2012
DOI: 10.1136/jclinpath-2012-200944
|View full text |Cite
|
Sign up to set email alerts
|

Her2 amplification distinguishes a subset of non-muscle-invasive bladder cancers with a high risk of progression

Abstract: A subset of high-grade NMIBCs contain Her2 amplification and are associated with markedly aggressive behaviour. Her2 diagnostics are valuable for distinguishing patients who require diligent surveillance and would potentially benefit from anti-Her2 therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 25 publications
9
49
3
1
Order By: Relevance
“…Separate studies have reported ERBB2 amplification predominantly based on FISH analysis in 8% to 9% of primary urothelial carcinomas, and at a higher frequency in lymph node metastases (20). In addition, in a study of non-muscle invasive bladder cancers, ERBB2 amplification has been observed in highgrade urothelial carcinomas (HG-UC) at a similar incidence of 9%, but not in any of the papillary urothelial neoplasms of low malignant potential or low-grade urothelial carcinomas studied, and has been associated with recurrence and progression in high-grade urothelial carcinoma (21). Her2 overexpression has been identified in 19% (22/116) of bladder cancers, with significant enrichment in grade III and muscle invasive tumors (22).…”
Section: Discussionmentioning
confidence: 99%
“…Separate studies have reported ERBB2 amplification predominantly based on FISH analysis in 8% to 9% of primary urothelial carcinomas, and at a higher frequency in lymph node metastases (20). In addition, in a study of non-muscle invasive bladder cancers, ERBB2 amplification has been observed in highgrade urothelial carcinomas (HG-UC) at a similar incidence of 9%, but not in any of the papillary urothelial neoplasms of low malignant potential or low-grade urothelial carcinomas studied, and has been associated with recurrence and progression in high-grade urothelial carcinoma (21). Her2 overexpression has been identified in 19% (22/116) of bladder cancers, with significant enrichment in grade III and muscle invasive tumors (22).…”
Section: Discussionmentioning
confidence: 99%
“…Twolevel (low and high) [44], 3-level (negative, 1+ and 2+) [44], and 4-level scales (0, 1+, 2+ and 3+) [45] have been used to assess the HER2 status. The cutoff value for IHC overexpression (3 + or strong) also varied from 10 [26] and 30% [28] to 40 [27] and 50% [45] in different studies.…”
Section: Issues In Her2 Assessment Methodsmentioning
confidence: 99%
“…It also pointed out that HER2 status in BC varies from 9% to over 80% in regards to protein overexpression and 0-32% regarding gene amplification (4-76 and 3-9% in NMIBC, respectively, in Table 1); furthermore, conflicting data exist regarding its prognostic relevance in BC [18,24,[26][27][28][29][30][31][32][33][34][35][36]. The reason for such variability of HER2 positivity is multifactorial, resulting from (a) tumor heterogeneity, with case series featuring varying tumor stages and histological grades (and different grading systems), (b) the diversity of methods used to assess HER status (amplification detection versus overexpression detection), (c) the technique used (polymerase chain reaction [PCR], in situ hybridization [ISH] and immunohistochemistry [IHC]) to assess HER2 status, and also (d) the specific definition given to HER2 "positivity" [24,37,38]; ethnic or geographic differences may account for further reasons [39].…”
Section: Her2 and Bcmentioning
confidence: 99%
“…Sjödahl et al [12] could not find an association between ERBB2 expression and the stage and grade of bladder cancer. Chen et al [19] could show that ERBB2 amplification could only be found in high-grade NMIBC and goes along with a more aggressive behavior and risk for progression. In this study, the researchers stratified only for low-risk and high-risk tumors.…”
Section: Discussionmentioning
confidence: 99%